Effect of mechanical strain on the pluripotency of murine embryonic stem cells seeded in a collagen‐I scaffold. Issue 2 (20th November 2017) - Hazenbiller, Olesja; Nasr, Saghar; Krawetz, Roman J.; Duncan, Neil A.
ABSTRACT: The use of embryonic stem cells (ESC) in regenerative medicine is restricted due to the possibility of tumorigenicity after inefficient or incomplete differentiation. Studies from our group, and others, suggest that mechanical stimuli may have a suppressive effect on the pluripotency/tumorigenesis of murine ESC (mESC). Furthermore, we have demonstrated that mESC seeded in a type I collagen scaffold, and transplanted into a murine bone fracture model, demonstrated repair without tumor formation. However, it remains unknown if mechanical factors were involved in blocking tumorigenicity of the mESC. Therefore, the aims of the current study were: (i) to characterize the mechanical environment within the transplanted construct (mESC‐Col I) in an in vivo murine fracture model using computational analyses; and (ii) to reproduce this mechanical environment in vitro to elucidate the role of these mechanical factors on mESC pluripotent gene expression. It was predicted that the mESC‐Col I construct was subjected to an average octahedral shear strain of ∼3.8% and a compressive strain of ∼3.1% within the fracture in vivo when the murine tibia was subjected to an axial compression load of 4 N (1 Hz). When a similar strain environment was replicated experimentally in vitro, the expression patterns of marker genes for pluripotency (Oct 4, Sox 2, Nanog, Rex 1, and oncogene ERas) were significantly down‐regulated. This suggests that the local micro‐mechanical environment within the fracture site in vivo may be involved in regulating stem cell fate after transplantation, and that these physical factors should be considered when developing regenerative medicine strategies. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:799–807, 2018.